Editorial: when the cloud computing becomes mobile! - Pathan, Al-Sakib Khan (Scientific Research Publishing Inc., 2013)
Handheld computing devices are now almost everywhere at the hands of technology dependent people of all ages. This rapid expansion of the number of mobile computing users has given rise of various research topics. Both the academia and the industries are looking for new ideas how to best-utilize the mobile computing power at the hands of consumers. While the technological advancements are going on from both hardware and software levels, novel concepts are also being introduced. One of those concepts is Mobile Cloud Computing (MCC).